Assessment of the Numerical Behavior of Remolded and Undisturbed Clayey Soil - Waheed Mohanned; Asmael Noor (Civil and Environmental Engineering)
The simulation of soil behavior using finite element analysis depends mainly on the input parameters considered in analysis, moreover, in the case of clayey soil, most of the experimental studies for small models are performed on remolded samples because of difficulty of providing undisturbed soils. This leads to unreal results for numerical analysis as the validation process of numerical results is performed on remolded sample.